Highly efficient capture of mercury from complex water matrices by AlZn alloy reduction-amalgamation and in situ layered double hydroxide - Fang, Yetian; Li, Fangyuan; Chao, Jingbo; Tang, Yang; Coulon, Frederic; Krasucka, Patrycja; Oleszczuk, Patryk; Hu, Qing; Yang, Xiao Jin (Taylor & Francis, 2023)
Mercury pollution is a critical, worldwide problem and the efficient, cost-effective removal of mercury from complex, contaminated water matrices in a wide pH range from strongly acidic to alkaline has been a challenge. Here, AlZn and AlFe alloys are investigated and a new process of synergistic reduction-amalgamation and in situ layered double hydroxide (SRA-iLDH) for highly efficient capture of aqueous Hg(Ⅱ) is developed using AlZn alloys. The parameters include the pH values of 1-12, the Hg(II) concentrations of 10-1000 mg L-1, and the alloy’s Zn concentrations of 20, 50 and 70% and Fe concentrations of 10, 20 and 50%. The initial rate of Hg(Ⅱ) uptake by AlZn alloys decreases with increasing Zn concentration while the overall rate is not affected. Specifically, AlZn50 alloy removes >99.5% Hg(Ⅱ) from 10 mg L-1 solutions at pH 1-12 in 5 min at a rate constant of 0.055 g mg-1 min-1 and achieves a capacity of 5000 mg g-1, being the highest value reported so far. The super-performance of AlZn alloy is attributed to multiple functions of chemical reduction, dual amalgamation, in situ LDH’s surface complexation and adsorption, isomorphous substitution and intercalation. This study provides a simple and highly efficient approach for removing Hg(Ⅱ) from complex water matrices.
Keywords: Mercury; Wastewater; Aluminum-zinc alloy; Reductive amalgamation; in situ layered doubled hydroxide